The evolution of digital photography as a popular culture through Instagram / Nur Shazleen Md Yusof and Mohamad Ridzuan Abdul Musa - Md Yusof, Nur Shazleen; Abdul Musa, Mohamad Ridzuan (2023)
Art means something beautiful, delicate, and soulful with certain elements and techniques. Photography means painting with light. An object or environment that is recorded using a camera, should have an element of light. Photography captures forms and events, both natural and artificial, to create a beautiful photographic art form that has values and meanings that match the importance of national culture and personality. In photography, light is captured and manipulated to express the idea, message, or emotion that can be interpreted as a form of art. With the progress of mobile technology, digital photography has reached a new pinnacle when the camera of a mobile phone is almost on par with the DSLR camera. This of course ushers in a new wave of photographers utilizing photography tools provided by their mobile devices.The photography in the digital era has become a popular culture due to the existence of mobile phones with high-resolution imaging cameras that are almost equivalent to professional DSLR cameras. At the end of 2010, the Instagram application was introduced by a company called Burbn Inc., led by CEO Mike Krieger and Kevin Systrom. At that time, only iPhone users could use the Instagram application. Later the Instagram application can also be used by Android smartphones, Windows Phones and also computer.